Practical design of steel structures based on Eurocode 3 (with case studies) : a multibay melting shop and finishing mill building - Ghosh, Karuna Moy (Whittles Pub. ; CRC Press, 2010)
Rigorous analysis of a complete structure
Keywords: Building, Iron and steel.; Structural design.; elektronické knihy; electronic books